Assessing the impact of fielding in Twenty20 cricket. Issue 8 (3rd August 2018) - Perera, Harsha; Davis, Jack; Swartz, Tim B.
Abstract : This paper attempts to quantify the importance of fielding in Twenty20 cricket. We introduce the metric of expected runs saved due to fielding which is both interpretable and is directly relevant to winning matches. The metric is assigned to individual players and is based on a textual analysis of match commentaries using random forest methodology. We observe that the best fielders save on average 1.2 runs per match compared to a typical fielder.